The Effect Of Peppermint Aromatherapy Onnausea, Vomiting In First Trimester Pregnant Womenat Bangetayu Health Center - Raina Lola Fauzia; Amanda Via Maulinda; Amelia Nur Hidayanti (LPPM AN NUUR, 2022)
Nausea and vomiting are common symptoms that are often found in first trimester pregnancy but can have an impact on the physical and mental condition of pregnant women. The incidence of nausea and vomitting in pregnant women in Bangetayu Health Center is 63 people. Peppermint aromatherapy can help to reduce nausea and vomitting. This study for to know the effect of peppermint aromatherapy on changes in nausea and vomitting in pregnant women with emesis gravidarum. Type of research is Quasy Ekasperiment, the one group pre post testdesign, samples of pregnant women gestational age 0 - 12 weeks with nausea and vomitting and selected by purposive sampling, data were tested with Paired t Test and Wilcoxon. P-value 0,000. There are influence of peppermint aromatherapy on changes in nausea and vomitting in pregnant women with emesis gravidarum. Pregnant women who experience nausea and vomitting are not normal to be able to use peppermint aromatherapy to reduce nausea and vomitting